2012
DOI: 10.22146/ijc.21349
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Poly(acrylamide-Co-Acrylic Acid)-Starch Based Superabsorbent Hydrogels by Gamma Radiation: Study Its Swelling Behavior

Abstract: Modification of poly (acrylamide-co-acrylic acid) superabsorbent hydrogels with varying starch concentration (1-3%) via simultaneous gamma radiation have been carried out. The structure and morphology of copolymers were characterization by Fourier transform infra red spectroscopy and scanning electron microscopy. The gel fraction, swelling kinetics and the equilibrium degree of swelling (EDS) of the hydrogels were studied. It was found that the an increase in the starch content present in the hydrogels (1-3%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 14 publications
1
14
0
1
Order By: Relevance
“…It is strongly suspected as the optimum dose range for the relatively large of the rate of absorption of hydrogels in this study. This is confirmed by our previous studies with increasing irradiation dose above 15 kGy caused the rate of absorption of the hydrogel decreased [10]. This is due to increasing irradiation doses, the density of crosslinked hydrogels increase and decreasing the rate of water absorption.…”
Section: Effect Of Immersing Of Time On the Swelling Of Hydrogelsupporting
confidence: 89%
See 4 more Smart Citations
“…It is strongly suspected as the optimum dose range for the relatively large of the rate of absorption of hydrogels in this study. This is confirmed by our previous studies with increasing irradiation dose above 15 kGy caused the rate of absorption of the hydrogel decreased [10]. This is due to increasing irradiation doses, the density of crosslinked hydrogels increase and decreasing the rate of water absorption.…”
Section: Effect Of Immersing Of Time On the Swelling Of Hydrogelsupporting
confidence: 89%
“…In addition, the acrylic acid containing carboxylic groups (COOH) as hydrophilic groups is easily binding with water molecules to form hydrogen bonds with water. Some researchers reported that acrylic acidbased superabsorbent hydrogel absorbs large amount of water with the rate swelling in the range of minutes, hours and days [10,[12][13][14]. Hence, it is indicated that the combination of starch with AAM-AA in the powder form of hydrogel prepared at a low irradiation dose (7.5 kGy) when compared with granular form (previous work) were greatly improved the capacity of hydrogels to absorb water.…”
Section: Effect Of Immersing Of Time On the Swelling Of Hydrogelmentioning
confidence: 99%
See 3 more Smart Citations